PROBLEMS OF TEACHER EDUCATION FROM A POSITION OF A RESEARCH UNIVERSITY - Igor V. Grebenev; Evgeny V. Chuprunov (Высшее образование в России)
The article deals with the issues concerning school education and teacher training higher education from the point of view of innovative University as a consumer and a customer of the results of these systems activities. The authors state their point of view on the ways to solve the current challenges of teacher education development, identify its significant problems and risks, describe the specificity of a modern pedagogical situation, point out the requirements of teacher training education, the structure of teacher’s professional competence. The article suggests the concept of teacher training at research University based on the leading role of scientific training, presents a new interpretation of a principle of scientific value in learning. Describes a possible role of the leading universities in formation the regional educational environment.